Digital Twin in Modelling Citronella Grass Essential Oil Distillation Process with Computational Fluid Dynamics Approach - Riwanti, Arifia Noor; Hermana, Budi (Green Engineering Society, 2024)
This study aims to investigate distillation process of Citronella Grass (Cymbopogon nardus) essential oil and determine the effect of heating temperature on oil quality, which significantly influences the market value. The study procedures were carried out by developing a virtual model of distillation apparatus using Digital Twin (DT) approach, integrating Computational Fluid Dynamics (CFD) to stimulate fluid behavior as it transitioned from vapor to liquid during distillation. The core of DT is in the virtual model development and three-dimensional (3D) geometric representations of system. The methodology comprised creating 3D geometric model of distillation setup, followed by mesh generation as well as setting of boundary conditions and computational parameters. In addition, numerical iterations were used to refine the process, leading to the analysis of CFD visualizations. The convergent result showed that the developed model was accurate at 300 iterations. Observations confirmed the occurrence of vapor to liquid phase change in the spiral pipe, with vapor density below 1 kg/m3 and liquid density between 800-1000 kg/ m3. Temperature monitoring showed a reduction from 120◦C in distillation tank to 24-26◦C post-condenser, which was similar to the observed range of 25-30◦C. Further temperature exchange in the reservoir was stimulated and observed in 36-38◦C. The result also showed that DT model created using CFD was capable of reflecting the real conditions observed.